Ali Baba Bujang Lapok - P. Ramlee, Tan Sri, 1928-1973 ([S.l.] : Malay Film Productions [production company] ; Kuala Lumpur : Sathya Productions [distributor])
Saksikan kisah lucu Ali Baba ( Aziz Satar ) bersama Ketua Penyamun ( P. Ramlee ) berserta dengan 40 orang kuncu-kuncunya.
Cast: P. Ramlee ( Chief ), Aziz Sattar (Ali Baba), S. Shamsuddin (Kassim Baba)
Keywords: Comedy films; Gangster films; Murder in motion pictures